Pengaruh Work Motivation, Burnout, Job Satisfaction dan Employee Engagement Terhadap Employee Performance - Citra Resdiyanti; Desy Prastyani (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to examine the influence of work motivation, burnout and job satisfaction on employee engagement and employee performance at PT Permodalan Nasional Madani. This research was motivated by employee performance which was not mentioned, so research was conducted to determine work motivation, burnout and job satisfaction, which are the variables that have the most influence on employee engagement and employee performance at PT Permodalan Nasional Madani. The population in this study consisted of permanent employees of PT Permodalan Nasional Madani in the Tangerang branch. Meanwhile, the research sample was taken using a purposive sampling technique with a total of 160 respondents. This research is quantitative research using the Structural Equation Model - Partial Least Square (SEM-PLS) method. The research results show that burnout has a positive effect on work motivation and employee engagement, while burnout has no positive effect on employee performance, then work motivation has a positive effect on employee performance but work motivation has no positive effect on employee engagement, then job satisfaction has a positive effect on employee engagement but Job satisfaction does not have a positive effect on employee performance, finally employee engagement does not have a positive effect on employee performance. After conducting research, the author suggested expanding the population to other branches, so that it could represent more answers from PT Permodalan Nasional Madani. Apart from that, you can also add other supporting variables, such as training, work environment, compensation, reward and punishment and other variables that are relevant to the novelty of the research.